BAGI HASIL DAN LABA BERSIH PADA PERBANKAN SYARIAH - Maria Sukma (Jurnal Ekonomi dan Bisnis, 2025)
The principle of profit sharing is an operational alternative that can be applied in banking activities to avoid usury by sharing in profits and losses based on Islamic sharia. The principle of profit sharing is based on the principle of At Ta awun, which is mutual help and cooperation among members of society for the good and the principle of avoiding Al Iktinaz, which is to withhold money (funds) and leave it idle that does not revolve in transactions that are beneficial to the general public. The principle of profit sharing (Syirkah) is applied in the mudharabah contract. Mudharabah consists of mudharabah mutlaqah and mudharabah muqayyadah. The distribution of profits in mudharabah financing is in accordance with the agreed ratio and is calculated based on gross income (revenue sharing) from the business results of the mudharib. Because the funds used in mudharabah financing mostly come from community funds (third party funds), Islamic banks must take steps to ensure that the funds of depositors used in financing are not harmed because the risk in profit-sharing financing is relatively high. Efforts to rescue troubled financing are carried out by restructuring financing through rescheduling, increasing financing facilities and temporary capital participation. Meanwhile, efforts to resolve troubled financing are carried out through collateral, financing write-offs and dispute resolution both through litigation and non-litigation (arbitration).